Pengaruh Lingkungan Kerja, Beban Kerja, Dan Motivasi Terhadap Kinerja Karyawan Di PT. Sun Hope Indonesia - Cristiana Vicensia Aritonang; Milda Handayani; Rini Wijayaningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Influence of Work Environment, Workload, and Motivation on Employee Performance at PT. Sun Hope Indonesia. This research aims to find out how much influence the work environment, workload and motivation have on employee performance which has an impact on PT. Sun Hope Indonesia This type of research is quantitative. The population in this study were all employees of PT. Sun Hope Indonesia in Jakarta. The sampling technique used Probability Sampling, data collection through distributing questionnaires directly and via Google from to 60 respondents, with data processing using SPSS version 27. Data that met the requirements was obtained using validity and reliability tests and classic assumption tests. The data analysis techniques used are multiple linear regression, t statistical test (partial), F test (simultaneous) and determatic test (R2). Based on the results of this research, it is stated that the Work Environment, Workload and Motivation simultaneously have a significant effect on the performance of PT employees. Sun Hope Indonesia. As well as the Work Environment variable partially having a positive and significant influence on employee performance and the Workload variable having a positive and significant influence on Employee Performance, the Motivation Variable having a positive and significant influence on Employee Performance. Based on this, it can be concluded that it is proven that the work environment, work load and motivation have a positive influence on employee performance. Each and every level of Work Environment, Workload, and Motivation has a positive influence on employee performance.